Pengaruh Kepercayaan dan Persepsi Risiko Terhadap Keputusan Pembelian pada Shopee di Denpasar - Diantari, Ni Putu Eka; Wijaya, Putu Yudy; Dewi, Ida Ayu Sasmita (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Growth of internet users, the development of business via internet media in Indonesia shows very good prospects, allowing sellers to effectively promote products and reach consumers widely. The factors that influence purchasing decisions are trust and risk perception. This research aims to determine the influence of trust and risk perception on purchasing decisions at Shopee in Denpasar City. The sample in this study, namely 100 Shoppe users, was tested using multiple linear regression analysis techniques. The results of this research show that Trust has a positive effect on Purchasing Decisions. Risk perception has a positive effect on purchasing decisions. From the research results, it is recommended for future researchers to further improve the shopping experience by actively participating in the Shopee online community, monitoring customer reviews, strengthening trust by following product updates and utilizing loyalty programs, as well as paying special attention to the security aspects of transactions; additionally, research can broaden the scope by exploring other variables such as brand, security, and convenience.